Dairy cattle farmers' preferences for different breeding tools - J.B. Clasen (Elsevier, 2021)
Breeding technologies play a significant role in improving dairy cattle production. Scientifically proven tools for improved management and genetic gain in dairy herds, such as sexed semen, beef semen, genomic testing, dairy crossbreeding, and multiple ovulation embryo transfer (MOET), are readily available to dairy farmers. However, despite good accessibility, decreasing costs, and continuous development of these tools, their use in Sweden is limited. This study investigated Swedish dairy farmers' preferences for breeding tools through a survey including a discrete choice experiment. The survey was distributed online to 1 521 Swedish farmers and by an open link published through a farming magazine. In total, the study included 204 completed responses. The discrete choice experiment consisted of 10 questions with two alternative combinations, which gave 48 combinations in total. Utility values and part-worth values were computed using a conditional logit model based on the responses in the discrete choice experiment for nine groups of respondents: one group with all respondents, two groups based on respondents using dairy crossbreeding or not within the past 12 months, two based on herd size, two based on respondent age, and two based on whether respondents had used breeding advisory services or not. The strongest preferences in all groups were for using sexed semen and beef semen. Genomic testing was also significantly preferred by all groups of respondents. Except in large herds, MOET on own animals was significantly and relatively strongly disfavoured by all groups. Buying embryos had no significant utility value to any group. Dairy crossbreeding had low and insignificant utility values in the group of all respondents, but it was strongly favoured by the group that had used dairy crossbreeding within the past 12 months, and it was disfavoured by the group that had not. Part-worth values of combined breeding tools showed that combinations of sexed and beef semen, alone or with genomic testing without dairy crossbreeding, were the most preferred tools. Compared with the most common combinations of breeding tools used in the past 12 months, the part-worth values indicated that Swedish dairy farmers may prefer to use breeding tools more than they do today. Statements on the different breeding tools indicated that the respondents agreed with the benefits attributed to the breeding tools, but these benefits may not be worth the cost of genomic testing and the time consumption of MOET. These valuable insights can be used for further development of breeding tools.